2017
DOI: 10.1038/s41598-017-01432-w
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Novel Zebrafish Model for Type 2 Diabetes Mellitus

Abstract: Obesity is a major cause of type 2 diabetes mellitus (T2DM) in mammals. We have previously established a zebrafish model of diet-induced obesity (DIO zebrafish) by overfeeding Artemia. Here we created DIO zebrafish using a different method to induce T2DM. Zebrafish were overfed a commercially available fish food using an automated feeding system. We monitored the fasting blood glucose levels in the normal-fed group (one feed/day) and overfed group (six feeds/day) over an 8-week period. The fasting blood glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
124
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(135 citation statements)
references
References 63 publications
6
124
1
4
Order By: Relevance
“…Among these, 46 genes were significantly downregulated and 30 genes were significantly upregulated in irf8 mutants compared to control siblings (Figure 4B). Several transcripts related to pancreatic and intestinal functioning (glucagon a and b, ghrelin, and insulin; Eames et al, 2013; Eom et al, 2013; Ye et al, 2015; Zang et al, 2017) were found to be downregulated in irf8 mutants, but these results were not reproduced by conventional qPCR analysis on additional gut samples (Figure 4C; data not shown). Such genes, which were deemed significantly changed by RNA-seq analysis but exhibited a large variation between the control replicates, were not considered or presented in the heatmaps (Figure 4C).…”
Section: Resultsmentioning
confidence: 95%
“…Among these, 46 genes were significantly downregulated and 30 genes were significantly upregulated in irf8 mutants compared to control siblings (Figure 4B). Several transcripts related to pancreatic and intestinal functioning (glucagon a and b, ghrelin, and insulin; Eames et al, 2013; Eom et al, 2013; Ye et al, 2015; Zang et al, 2017) were found to be downregulated in irf8 mutants, but these results were not reproduced by conventional qPCR analysis on additional gut samples (Figure 4C; data not shown). Such genes, which were deemed significantly changed by RNA-seq analysis but exhibited a large variation between the control replicates, were not considered or presented in the heatmaps (Figure 4C).…”
Section: Resultsmentioning
confidence: 95%
“…The blood glucose range of zebrafish is similar to that for humans, spanning approximately 40-300 mg/dL in extreme cases with normal physiological levels around 70-80 mg/dL. 13 In addition, high glucose levels in fish stimulate insulin expression, as in humans, 14,15 and the fish glucose transporter genes Glut2 and Glut4 show significant conservation of structure, function, and glucose affinity with human orthologs. 16,17 The development and function of two key organs involved in diabetes, the pancreas and liver, is significantly conserved between mammals and zebrafish.…”
Section: Glucose Metabolism In Zebrafishmentioning
confidence: 95%
“…This model is promising especially because the symptoms can be ameliorated with antidiabetic drugs like metformin and glimepiride. 15 It is also possible to elicit hyperglycemia simply by immersing the fish in 1%-2% glucose solutions. The glucose-immersed zebrafish mimic the fluctuations in blood glucose levels of human diabetic patients and develop specific retinal lesions in a relatively short period of time.…”
Section: Glucose Metabolism In Zebrafishmentioning
confidence: 99%
See 2 more Smart Citations